MET expression and copy number status in clear-cell renal cell carcinoma: prognostic value and potential predictive marker - Macher-Göppinger, Stephan; Keith, Martina; Endris, Volker; Penzel, Roland; Tagscherer, Katrin; Pahernik, Sascha; Hohenfellner, Markus; Grüllich, Carsten; Schirmacher, Peter; Roth, Wilfried (OncoTarget, 2017)
Oncotarget | https://doi.org/10.18632/oncotarget.13540 Stephan Macher-Goeppinger, Martina Keith, Volker Endris, Roland Penzel, Katrin E. Tagscherer, Sascha Pahernik, Markus Hohenfellner, Humphrey Gardner, Carsten...